HUBUNGAN HUKUM ANTARA NASABAH PENYIMPAN DANA DENGAN BANK DALAM PRESPEKTIF HUKUM PERJANJIAN DI INDONESIA - Hendri Jayadi; L. Elly A. M Pandiangan (to-ra, 2018)
The legal relationship between the customer and the bank occurs after both parties sign an agreement to utilize the service products offered by the bank. Every bank product always has provisions offered by the bank. The agreement between the customer and the bank is binding. The customer, as the depositor of the funds, saves his funds in the bank and gives the bank freedom to manage the money or the funds it holds. The legal relationship between banks and customers is regulated in Article 1 paragraph (5) of Law no. 10 of 1998, set forth in the form of an 'agreement' or 'contract' must use the four principles of duciary relation principle, prudential principle, secrecy principle, and know how customer principle. So that the customer relationship with the Bank is about law and trust. Keyword : customer; bank depositor; prudential; law and trust.